Communication of Leadership and Group Conformity in Community Forest Management - Ike Rosmanita; Sarwititi Sarwoprasodjo; Rina Mardiana (HABITAT, 2021)
The utilization of forest areas, especially in production forest areas managed by Perhutani, provides benefits to communities around the forest. The Collaborative Forest Management Program (PHBM) is supposed to improve community welfare and forest sustainability. Studies on the environment or forest area, group conformity (adjustment), and environmental values used by farmer groups in forest management practices can be analyzed using environment communication. The purpose of this research: Profile Mitra Tani Sejahtera group of forest village community associations (PMDH); Analyze relationship characteristics (cohesiveness and style of leadership) between forest management behavior of farmer groups; Analyze relationship conformity between forest management behavior farmer group; and Analyze environment values with forest management behavior. This research was conducted at the Mitra Tani Sejahtera group in Kediri. This study had 100 respondents using a random sampling system. Sampling from population data begins with determining the sample size using the Slovin formula. Data collection was carried out using questionnaires and closed interviews, and FGD. Data analysis used the Pearson correlation test to determine the relationship between variables. The results showed that the Pearson correlation coefficient between the cohesiveness and forest guarding behavior was .549 **. There is a correlation between cohesiveness and forest protection behavior of 0.549. leadership style related to community behavior in protecting the forest by .245 **. The Result shows is a relationship between group characteristics (cohesiveness and leadership style) with the practices of maintaining forest security because of the sense of kinship in the group and a democratic leadership style. Conformity has a relationship with practices maintaining forest security because it complies with the rules made by Perhutani. Environmental values have a relationship with management forest security behavior because of a sense of cooperation within the group.